PENDUGAAN CADANGAN KARBON DI ATAS PERMUKAAN TANAH DI AREAL KAMPUS UNIVERSITAS NUSA BANGSA - Farmen, Handi; Panjaitan, Poltak BP; Rusli, Abdul Rahman (Jurnal Nusa Sylva, 2014)
The objective of this study was to determine the amount of carbon in the surface soil that can be absorbed by the vegetations in the all area of Nusa Bangsa University (UNB). This research was conducted in the UNB’sarea with its boundary is equal limits of the UNB’s area thattotal area UNB’s is 12,082 m2. Data inventoried from UNB area is undergrowth class,little, middle and big tree class and also palmae class.The results of this study showed the amount of carbon absorbed on the surface vegetation in the UNB campus is at 61.8 tonnes of carbon which absorbed by the undergrowth class (diameter <2 cm), 59 species of woody plants (diameter> 2 cm) consisting of 284 individual and 7 types palmae group consisting of 94 individuals.